Review of Artificial Intelligence and Natural Man, by Margaret Boden - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Review of Artificial Intelligence and Natural Man, by Margaret Boden." Philosophy of Science 45 (1978): 648-49.